The Cross-sectional Area of Tendo Achilles as Measured by Diagnostic Ultrasound - Amin, Sanjida; Ara, Shamim; Begum, Shahanaz; Ahmed, Afroz; Akhter, Tazrin; Epsi, Effat Zerin (Bangladesh Journal of Anatomy, 2016)
Context: Morphology of tendo achilles can be measured in vivo and in vitro. In vitro by dissection methods, specimen are usually used. In vivo radiological measurement is most commonly practiced. In radiological aspect X-ray, Magnetic Imaging Resonance (MRI), Computed Tomography (CT) scan, ultrasonography are the recommended methods of tendo achilles measurement. All the measurements of tendo achilles vary with age, body height of the subjects and the dominance of the ankle. Aging is associated with a marked change in tendon measurements. With advancing age, there is a decrease in the size but increase in the fibril concentration of tendon thus the cross-sectional area of tendo achilles in older subjects is relatively larger. Older people and dominant ankles tend to have tendo achilles with a larger cross- sectional area. So the cross- sectional area is more accurate than the tendon thickness in assessing variations of tendon size. The aim of the study was to establish the standard reference values for the cross-sectional area (CSA) of tendo achilles as measured by diagnostic ultrasound in several age groups of sedentary people. Materials and Methods: This is a cross sectional analytical type of study conducted in the Department of Anatomy Dhaka Medical College Hospital from July 2013 to June 2014.The present study was performed on 200 tendo achilles of 100 people (among them 50 were male and 50 were female). They were randomly selected from the patients who came to the Radiology Department of Dhaka Medical College Hospital for ultrasonography of any regions of their body other than leg. Result: Highly significant difference was observed between the cross-sectional area of tendo achilles of right and left leg in male and female (p<0.001). Cross sectional area was more in male than that of female and cross-sectional area was larger in left tendon than that of right. In the present study highly significant correlation was observed between the cross-sectional area of tendo achilles with age (p<0.001). Crosssectional area of left tendo achilles of the age group of 50 to 65 years was significantly higher than that of other age groups (P < 0.05). But statistically no significant difference was found between the crosssectional area of right dominant and left dominant leg (p>0.05). Conclusion: The data of cross-sectional area of tendo achilles obtained from the present study may provide valuable information in different aspects of medical science as a guide line for physiotherapists, radiologists, sports professionals, ortho-surgeons in early detection and monitoring the rehabilitation of professional athletes. Bangladesh Journal of Anatomy January 2016, Vol. 14, No. 1, pp. 22-27